Pengaruh BebanKerja, Lingkungan Kerja Dan Pengawasan Terhadap Stres Kerja Karyawaan PT. Daya Manunggal Salatiga Departemen Weaving AJL II - Rizky Aujada; Saryadi Saryadi; Hari Susanta Nugraha (Universitas Diponegoro, 2015)
Work stress is a response from a person, both physically and mentally to a change in the environment that is felt disturbing and resulted in his being threatened. Every aspect at work can be a stressor. Stressful conditions can cause health problems or make existing problems become more severe. Stress is caused by a trigger or stimulus, called stressors, stressors can come from ourselves or from outside ourselvesThe sampling technique used is Probability Sampling and the sampling type used is Proportionate Stratified Random Sampling. Sample in this research is 62 respondents consisting of employees of PT. Manunggal Daya Salatiga Weaving Department AJL II. Data analysis using analysis quantitative with validity and reliability , simple regression analysis, double regression analysis, t test and f test with program spss 18.0 for windows.The results of research shows that there is a positive effect and significant between the workload to work stress amount 79,5%, the work environtment have positive effect and significant to work stress amount 68,5% and the controlling have positive effect and significant to work stress amount 71%Advice can be given in this research are the company must keep existing stressor so that employees rarely or never experience stress. Companies can increase the quantity of the workload but must pay attention to whether it becomes overloaded workload for employees. Besides keeping the stress caused by the work environment and poor controlling.